Möglichkeiten zur Kompensation der kalten Progression: Wirkung in Österreich - Dénes Kucsera; Hanno Lorenz (Wirtschaftsdienst, 2016)
Die Zusatzbelastung der Lohnsteuerpflichtigen durch die kalte Progression wird seit der Steuerreform 2016 bis 2021 in Österreich 6,2 Mrd. Euro erreichen. Es folgt ein Überblick darüber, wie andere Länder mit dem Problem der kalten Progression umgehen und wie sich die Anwendung dieser Maßnahmen für Österreich auswirken würde. Je nach Anpassungsmodell kann die kalte Progression bis 2021 auf 4 Mrd. Euro abgesenkt werden oder sogar die österreichischen Steuerzahler um 1,6 Mrd. Euro entlasten. Für eine Eliminierung der kalten Progression müssten der Tarifverlauf sowie Frei- und Absetzbeträge jährlich und vollständig an die Inflation angepasst werden. – – Regardless of the latest tax reform the fi scal drag brings an additional tax burden of exteuro 6.2 billion for the period 2016-2021 to Austrian taxpayers. In 2021 alone this fiscal drag will levy an additional exteuro 2.17 billion. The study in hand gives an overview how other countries control the fiscal drag and analyses the effect of such adjustments in the Austrian tax system. Depending on the adjustment model, the range of the fiscal drag by 2021 lies between a tax burden of exteuro 4 billion (tax brackets adjusted once the cumulative inflation reaches the 5 percent threshold) and between a tax reduction of exteuro 1.6 billion (the tax system is adjusted to the development of nominal wages). In the latter case an adjustment leads to an over-compensation of the fiscal drag yielding a constant tax burden relative to income. For the entire elimination of the fiscal drag an annual infl ationary adjustment of the tax brackets, tax credits and deductibles is necessary.
Keywords: H20; H21; 330